Investigación y formación docente en la educación superior. Tensiones y desafíos (2015)
This reflection paper presents the results of the Scientific and Technological Research Project (PICT -2007- 02029) in which three Argentine universities and three teacher training institutions participated. In the paper we analyze the research findings belonging to the National University of San Luis. (Node 2 UNSL) The main objective was to develop an outlook that analyzes different regional perspectives on teacher training in areas marked by social inequality.The research team adopted the methodology of collaborative research network. From this approach, the network enables a dynamic exchange between individuals, groups and institutions. It is an open system, which is in construction, and involves sets that identify common needs and problems, and are organized to strengthen their resources and encourage collaborative participation.This paper is addressed to one of the research interests of the research team: the problem of the relationship between research and teacher training in a unique setting: the Institute of Teacher Education San Luis.Although in recent decades a clear political intention to install research practice in teacher training institutes is observed, this has presented unique settings in the institution analyzed. We can say that although there are certain novel institutional conditions that favor the research, research-teaching relationship is perceived by institutional actors as a tense relationship. This tension points definitively to the meanings attributed to teaching and its relationship to the construction of knowledge.